Ultrasonographic appearance of normal and injured lateral patellar ligaments in the equine stifle. (29th May 2015) - Gottlieb, R.; Whitcomb, M. B.; Vaughan, B.; Galuppo, L. D.; Spriet, M.
Summary: Reasons for performing study: Ultrasound is widely used in horses with stifle lameness, yet limited information is available regarding the appearance of normal and injured lateral patellar ligaments (LPL). Objectives: To map the normal ultrasonographic appearance of the LPL. To describe the clinical and ultrasonographic features of LPL injuries. Study design: Descriptive study of healthy horses and retrospective case series. Methods: Twelve horses without stifle lameness underwent ultrasonographic examination of bilateral LPLs and ultrasonographic features were recorded. Eighteen horses with LPL injury were identified from 1999 to 2011. Results: The normal LPL changes in appearance from origin to insertion. It shows ill‐defined margins at the patella, becomes flattened and bilobed over the lateral trochlear ridge, is oval‐triangular shaped with variable echogenicity and fibre pattern distal to the LTR, and becomes tapered with striations at the tibial insertion. LPL injury was identified in 18 horses of multiple breeds and uses. All injuries were acute, and 12 had wounds. Eleven horses were severely lame ( grade 4–5/5 ). Ultrasonographic lesions were severe in 78% of cases. The mid to insertional portion of the LPL was most often affected. Radiography showed fractures of the tibial tuberosity (n = 6), patella (n = 4) and lateral trochlear ridge (n = 1). Fractures involved LPL attachments in 9 horses. Five were treated for osteomyelitis and one for synovial sepsis. Recheck ultrasound in 4 horses showed minimal to no change in the appearance of LPL injuries. Nine horses returned to riding, one continued as a broodmare, 2 were retired, one became a broodmare, 2 were lost to follow‐up and 3 were subjected to euthanasia owing to concurrent injuries. Conclusion: Normal variations in shape, echogenicity and fibre pattern of the LPL are important considerations to prevent false positive diagnoses during ultrasonography. LPL injuries were often severe and associated with craniolateral stifle trauma. Prognosis varied from good to guarded in horses without additional severe injuries.